Analisis Struktur Pertunjukan Opera Batak Sisingamangaraja XII: Episode Tongtang I Tano Batak - Rosta Minawati; Enrico Alamo; Sherli Novalinda; Sulaiman Sulaiman (LP2M ISBI Bandung, 2019)
ABSTRACTOpera Batak is a “traditional” performance genre from the Toba Batak ethnic group. Opera Batak is staged based on oral tradition through acting, music and dance. The creation of works aims to preserve Sisingamangaraja XII's historical values. The method is carried out beginning with research through observation, interviews, literature studies with steps to work on the search phase, the stage of giving content, the development stage, and the stabilization stage.Transitions of performers and sections are accompanied musical instruments including gondang, suling, serunai, kedapi, hesek, odap and garantung. This mixture is intended to bring the drama to life and entertain the audience. The figures in Opera Batak are Sisingamangaraja XII, Patuan Anggi, Putri Lopian, Boru Sagala, Somaling, Panglima Sarbut and Panglima Amandopang. his episode tells how the war against the Dutch company in the Batak land for about 30 years. Arranged with a flow, dramatic, and conflicting conflict to show Sisingamangaraja's humanity and kinship side in the face of war.Key Word: Opera Batak, Theater, Sisingamangaraja XII, Tongtang I Tano BatakABSTRAKOpera Batak merupakan seni pertunjukan ‘tradisi’ dalam masyarakat Batak.Opera Batak ditampilkan melalui sastra lisan, pemeranan, musik, dan tarian. Penciptaan karya bertujuan untuk melestarikan nilai-nilai kesejarahan Sisingamangaraja XII. Metode dilakukan diawali dengan riset melalui observasi, wawancara, studi pustaka dengan langkah garap; tahap pencarian, tahap memberi isi, tahap pengembangan, dan tahap pemantapan. Opera Batak dipandu pencerita dalam mengenalkan tema, menyapa penonton, menggambarkan kisah, dan menggenalkan pemain. Peralihan pemain dan bagian diiringi musik yang terdiri atas: gondang, suling, sarunai, kecapi, hesek, odap, dan garantung. Tokoh Opera Batak dalam episode Tongtang I Tano Batak adalah Sisingamangaraja XII, Patuan Anggi, Putri Lopian, Boru Sagala, Somaling, Panglima Sarbut, dan Panglima Amandopang. Episode ini menceritakan bagaimana perperangan melawan kompeni Belanda di tanah Batak yang kurang lebih 30 tahun lamanya. Disusun dengan alur, dramatik, dan konflik yang rapat untuk memperlihatkan sisi kemanusian dan kekeluargaan Sisingamangaraja dalam menghadapi perperangan.Kata Kunci: Opera Batak, Teater, Sisingamangaraja XII, Tongtang I Tano Batak